Incidence, Duration, and Management of Anemia: A Nationwide Comparison Between IBD and Non-IBD Populations. Issue 6 (27th September 2019) - Patel, Dhruvan; Yang, Yu-Xiao; Trivedi, Chinmay; Kavani, Himanshu; Xie, Dawei; Medvedeva, Elina; Lewis, James; Khan, Nabeel
Abstract : The first study evaluating the duration of time inflammatory bowel disease (IBD) patients spent in an anemic state (52 days/year in IBD patients vs 27 days/year in non-IBD patients). More efforts need to be made to recognize and treat anemia in IBD patients. Abstract: Background: Although the prevalence of anemia has been extensively studied in the inflammatory bowel disease (IBD) population, no study has evaluated the duration of time IBD patients remain anemic over the course of their disease. Our aims were to determine the incidence, duration of anemia, and rate of receipt of iron therapy among IBD patients and compare these with non-IBD patients. Methods: We conducted a retrospective nationwide cohort study among the US veteran population from January 2011 to September 2018. Inflammatory bowel disease patients who were not anemic at the time of first IBD medication were included and matched with non-IBD patients. We estimated the incidence of anemia, duration of time patients spent in an anemic state per year, and rate of anemia treatment among IBD and matched non-IBD patients. Results: A total of 3114 IBD patients were included and matched to 5568 non-IBD patients. The incidence rate of anemia was 92.75 per 1000 person-years in the IBD group vs 51.18 per 1000 person-years in the non-IBD group. The mean (SD) number of anemia days per year in the IBD and non-IBD groups was 52.5 (82.1) and 27.3 (62.4), respectively ( P ≤ 0.001). Although anemic IBD patients were more likely to receive iron therapy compared with non-IBD anemic patients, only 37% and 2.8% of anemic IBD patients received oral or intravenous iron therapy during follow-up, respectively. Conclusions: Inflammatory bowel disease patients spent almost 2 months of each year of follow-up in an anemic state. Greater efforts are needed to decrease the duration of time patients remain in an anemic state.